Design of a low-power microcontroller-based wireless ECG monitoring system - Fariborzi, H.; Moghavvemi, M.; Mehrkanoon, S. (2007)
The design and implementation of a smart wireless sensor for remote monitoring of electrocardiogram (ECG) is proposed in this paper. The objective of this system is to provide unobtrusive real-time healthcare for cardiac patients who are in normal life setting, like home or work place. In the heart of the system an ultra-low-power microcontroller is used to control all other units like the transceiver, external flash memory, PC interface, etc. A novel algorithm has been developed to detect life threatening events before transmission of signals to the nearby computer. This feature is useful for power consumption reduction since the system can be programmed to transmit only abnormal beats and rhythms. Moreover, it enables the system to work even outside the reliable radio range of the local PC.